KERENTANAN SOSIAL EKONOMI DAN BIOFISIK DAERAH ALIRAN SUNGAI SOLO (Socio-economic and biophysical vulnerability of Solo Watershed) - Nur Ainun Jariyah; Irfan Budi Pramono (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2018)
ABSTRACTIncreasing degradation of watershed ecosystem is a problem that needs to be resolved. Therefore, a study was conducted in order to determine the socio-economic and biophysical vulnerability of Solo watershed in relation to watershed management. This research was conducted in Solo Watershed. The collected data include primary and secondary data. The potential and vulnerability of socio-economic and biophysical were evaluated using the The Formulation of Watershed level Characterization System. The results of the study showed that (1) the socio-economic of the whole Solo watershed classify as moderate category, with the highest vulnerable district was Wonogiri due to high population density and high land vulnerability, (2) land vulnerability for the whole Solo watershed is in the medium category, with the most vulnerable land category was in Madiun and upstream Solo sub-watersheds, (3) the most prominent flood vulnerability was in the downstream of Solo sub-watershed, (4) the typology of watershed management was classified as high vulnerable because the territorial typology was in the very high vulnerable and the watershed typology was medium vulnerable. By knowing its vulnerability level, the rehabilitation program can be directed to areas with a high level of vulnerability.Keywords: socio-economic; biophysical; vulnerability; watershed management ABSTRAKKerusakan ekosistem Daerah Aliran Sungai (DAS) yang semakin meningkat merupakan permasalahan yang perlu diselesaikan. Oleh karena itu telah dilakukan penelitian yang bertujuan untuk mengetahui kerentanan sosial ekonomi dan biofisik Daerah Aliran Sungai (DAS) Solo dalam kaitannya dengan pengelolaan DAS. Penelitian ini dilaksanakan di wilayah DAS Solo. Data yang diambil meliputi data primer dan sekunder. Potensi dan kerentanan sosial ekonomi serta biofisik dievaluasi dengan menggunakan formulasi Sistem Karakterisasi Tingkat DAS (Tipologi DAS). Hasil penelitian menunjukkan bahwa (1) tipologi sosial ekonomi keseluruhan DAS Solo termasuk dalam kategori sedang dengan kabupaten yang sangat rentan adalah Wonogiri yang dipicu oleh kepadatan penduduk dan kerentanan lahan yang tinggi, (2) kerentanan lahan di DAS Solo secara menyeluruh termasuk dalam kategori sedang dengan tingkat kerentanan lahan yang paling tinggi di Sub DAS Kali Madiun dan Solo Hulu, (3) kerentanan banjir paling tinggi di Sub DAS Solo Hilir, (4) tipologi pengelolaan DAS Solo secara keseluruhan termasuk dalam kategori kerentanan tinggi karena tipologi kewilayahan termasuk dalam kategori kerentanan sangat tinggi dan tipologi DAS termasuk dalam kategori kerentanan sedang. Dengan mengetahui tingkat kerentanan suatu DAS maka kebijakan program rehabilitasi dapat diarahkan ke daerah-daerah yang mempunyai tingkat kerentanan yang tinggi.Kata kunci: sosial ekonomi; biofisik; kerentanan; pengelolaan DAS